RIMPANG KECOMBRANG (Etlingera elator Jack.) SEBAGAI SUMBER FENOLIK - Syarif, Rezki Amriati; Sari, Firdha; Ahmad, Aktsar Roskiana (Jurnal Fitofarmaka Indonesia, 2016)
Kecombrang (Etlingera elatior Jack.) is one of the plants growing in the area of Palopo, South Sulawesi. Kecombrang included in the Zingiberaceae family and rhizome of kecombrang widely used by the community as an antioxidant. This research aimed to determine the phenolic content on the methanol extract of the rhizome kecombrang. Methanol extract of rhizhome kecombrang obtained by maceration method with methanol P. Chemical component analysis used thin layer chromatography (TLC) is characterized by the appearance of spot. Determination of the phenolic content of the methanol extract of rhizomes kecombrang used the TLC-densitometry. The results showed that the phytochemical assay on methanol extract of kecombrang rhizomes positively countains 144.43 Âµg phenolic compounds.